PENGEMBANGAN MODUL SUB MATERI PERAN TUMBUHAN DI BIDANG EKONOMI DENGAN INFORMASI PEMBUATAN ROTI ISI PEPAYA - Sari, Ratika; Daningsih, Entin; Yokhebed, Yokhebed (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aimed to develop module and to know students’ response to module submaterial plant role in economy with addition making of bread containing papaya. This research used Research and Development (R & D) method, consisting of six out of ten stages, namely potential and problems, data collection, product design, design validation, design revision and limited trials. The modul was evaluated by five validators consisting of two biology lecturers and three teachers from secondary high schools. The student’s response to module submaterial plant role in economy used a response questionnaire with ten statements. Result of validation showed 0.96 of CVI value and categorized valid. Obtained 85.1% and categorized very high. Therefore, the module sub material plant role in economy can be used in learning process. Keywords : Bread containing papaya, module, R&D method, responses.